Micromorphological Study of Concotto Surfaces Protected by the Avellino Eruption in 3945 ± 10 cal. BP at the Early Bronze Age of Afragola Village in Southern Italy. (2nd October 2017) - Matarazzo, Tiziana; Berna, Francesco; Goldberg, Paul
ABSTRACT: The term Concotto refers to fragments or patches of hard heated clay that derive from living surfaces, walls, and ovens. Concotto fragments are found throughout the Italian peninsula and date from the Neolithic to the Iron Age. Current studies express contradictory opinions about whether or not the Concottos on living surfaces represent intentionally constructed surfaces or the secondary products of the contact between hot embers and sediments. This study uses micromorphological analysis to investigate the function and composition of Concotto surfaces from several domestic structures at the Early Bronze Age village of Afragola in southern Italy. Afragola is an exceptionally preserved agricultural village that was covered by almost 1 m of volcanic ash during the Vesuvius eruption in 3945 ± 10 cal. BP. The Concottos at Afragola are hard, red surfaces that are typically associated with burned materials. Micromorphological analysis reveals that the Concottos were intentionally made by laying down patches of clay and then heating them to create a hard, flat surface. This study explores the potential uses of the Concotto as cooking surfaces during the Early Bronze Age of southern Italy.